Impacto de la gestión financiera y su incidencia en la rentabilidad de la empresa telecable Iquitos SAC periodo 2019 - Panduro Casado, Jorge Luis (2022)
The main objective of this research work was to analyze the financial management and its impact on the profitability of the company Telecable Iquitos SAC, period 2019, for which a quantitative type research has been developed, since management data was collected and analyzed. financial and profitability, with a non-experimental research design and a transactional type of design; Regarding the population and sample of the investigation, it was made up of the financial statements and 30 workers of the company; concluding that financial management has a positive impact on profitability, since according to the results obtained from the survey of workers they have a high rate of knowledge of financial management; with more than 80% of affirmative answers, and with respect to profitability, the results obtained from the documentary analysis concluded that for financial profitability (ROE) the net profits of the company corresponded to 50% of the assets, that is, the partners obtained a return on your investment of 50%, and for the economic profitability (ROA), with respect to the company's total assets, its sales corresponded to 31%, that is, each sol invested in total assets generated 31 soles of net profit; then, performing the comparative analysis of the profitability indicators, it was identified that the ROE (50%) is greater than the ROA (31%), which allows the company to obtain financial debt to generate profitability that benefits investors.